Estudo comparativo do comportamento alimentar em diferentes hospedeiros e de componentes bioativos da saliva de Cimex lectularius Linnaeus, 1758 e Cimex hemipterus (Fabricius, 1803) (Hemíptera, Cimicidae) - Fernanda Silva Costa (2007)
Cimex lectularius and Cimex hemipterus are the main species of cimicidae associated with humans. In the present study, the electrical signal of the cibarial pump while feeding in different sources, the anticoagulant activity and the amount of proteins (total and hemeproteins) of the salivary gland homogenate from these two species were comparatively evaluated. The weight gain and the total contact time from C. lectularius fed in mice were higher in females than in males, although the ingestion rate was similar in both sexes. Comparing both species, C. lectularius presented better feeding performance in live hosts (pigeon and mice) than C. hemipterus. This last species had more difficulty to obtaining blood from pigeon than from mice. The treatment of the pigeon with an anticoagulant increased the total ingestion rate and the percentage of C. hemipterus that doubled the weigh. The effective ingestion rate from C. lectularius was higher in an artificial feeder than in mice. The differences found on the feeding performance between the two species could be related to the higher anticoagulant activity and concentration of hemeproteins present in the salivary gland of C. Lectularius in comparison to C. hemipterus.